Feasible joining on the reaction layer of diffusion bonded sialon and duplex stainless steel - Haris, F. (Asian Research Publishing Network, 2016)
The main objective of this work is to analyse the feasible joining in microstructure and the interdiffusion of elements on the reaction layer of diffusion bonded sialon with duplex stainless steel. Combination of these two materials is a complex task due to dissimilar in thermal expansion coefficient. Diffusion bonding of sialon and duplex stainless steel was conducted by applying pressure of 16 MPa at 1200 Â°C for 30 minutes and 1 hour in a vacuum hot press furnace. The reaction layer that connected sialon and duplex stainless steel was analysed using optical microscopy and scanning electron microscope for its microstructure while energy dispersive x-ray was used for elemental diffusion analysis. The samples of 30 minutes and 1 hour diffusion bonding time show good joining were attained due to ductile layer. Formation of pearlite near to the steel was also revealed in both samples. Small gaps can be discovered on the reaction layer in 30 minutes diffusion bonding time as compared to 1 hour. However, the joining on both samples remained intact due to presence of reaction layer. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.